Sekolah Sepakbola Di Pekanbaru Dengan Pendekatan Struktur Sebagai Elemen Estetika - Herhandiqa Herhandiqa; Wahyu Hidayat; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Football is the most wanted sport in Indonesia especially for the male population. But, lack of football prestation in the International cauldron not proven a great satisfaction, so it need an practice place for young atlete and teenager. Football school is one of another choice that can make a change football prestation to be high gradiance in international cauldron. With this football existance expected can build an efective facility and room for the user and visitor, so this football school design plan can prove the incridible spirit to the young generation who love Indonesia football. In this football school design,Approach structure as aestethic that applied in the design, such as: (1) Ornament Structure; (2) Structure as Ornament; (3) Structure as Arcitecture; (4) Structure as former producer; (5) Denial Structure. Tikitaka and Crossing concept was choosen to solve every problem occur during the Football school in Pekanbaru processed. This concept was applied in every single arcitectural aspect in Football school design in Pekanbaru, such as: composision mass, mass former, then building faced. Simple reguler mass, former mass and building faced is the application goal from analogy concept, former football strathegy “tikitaka” and “crossing”. Keywords: football school, analogy strategy tikitaka and crossing, structure as aesthetic element.